The Analysis of MPV, Plateletcrit, Platelet Distribution Width, and Total Platelets in AKI - Ellen Kurniawati Tungka; Yuyun Widaningsih; Fitriani Mangarengi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Patients with Acute Kidney Injury (AKI) who require hemodialysis had been reported to have a mortality rate of 50-70% in the last 30 years. Platelet and platelet index are two of the important hematological markers to be analyzed in AKI. This study aimed to analyze the levels of MPV, PCT, PDW, and total platelets in patients with AKI. A retrospective study using medical record data of 122 patients with AKI from January 2019 to December 2020 was conducted in Dr. Wahidin Sudirohusodo Hospital, Makassar. Patients were grouped based on disease outcomes and consisted of patients who died in the hospital and patients who recovered. Measurement of MPV, PCT, PDW, and platelet count was performed using a hematology analyzer. Mann-Whitney and independent T-tests were used for statistical analysis. The subjects of this study consisted of 80 AKI patients who died and 42 who recovered, the most affected age was > 56 years old. The mean MPV was significantly higher in subjects who died in the hospital (10.31±1.53 fL) than in patients who recovered (9.5±1.39 fL) (p<0.01). Mean PCT was higher in subjects who died in the hospital (0.85%) than in patients who recovered (0.18%), despite statistical insignificance (p>0.05). Mean PDW was higher in subjects who died in the hospital (14.2 fL) than in patients who recovered (13.2 fL), despite statistical insignificance (p>0.05). Mean platelet was lower in subjects who died in the hospital (174.3 x109L) than in patients who recovered (215.6 x109L), despite statistical insignificance (p>0.05). Mean platelet volume levels were elevated in AKI patients with poor outcomes, possibly associated with the pathogenesis of more severe inflammation caused by hyperaggregation and peripheral destruction of platelets, which provide positive feedback to the bone marrow to produce larger and more active platelets. The MPV levels were significantly higher in AKI patients with poor outcomes, whereas PCT, PDW, and total platelet levels were not significant.